Memory's Daughters : The Material Culture of Remembrance in Eighteenth-Century America - Stabile, Susan (Book collections on Project MUSE., 2018)
A renowned literary coterie in eighteenth-century Philadelphia--Elizabeth Fergusson, Hannah Griffitts, Deborah Logan, Annis Stockton, and Susanna Wright--wrote and exchanged thousands of poems and maintained elaborate handwritten commonplace books of memorabilia. Through their creativity and celebrated hospitality, they initiated a salon culture in their great country houses in the Delaware Valley. In this stunningly original and heavily illustrated book, Susan M. Stabile shows that these female writers sought to memorialize their lives and aesthetic experience--a purpose that stands in marked contrast to the civic concerns of male authors in the republican era.Drawing equally on material culture and literary history, Stabile discusses how the group used their writings to explore and at times replicate the arrangement of their material possessions, including desks, writing paraphernalia, mirrors, miniatures, beds, and coffins. As she reconstructs the poetics of memory that informed the women's lives and structured their manuscripts, Stabile focuses on vernacular architecture, penmanship, souvenir collecting, and mourning.Empirically rich and nuanced in its readings of different kinds of artifacts, this engaging work tells of the erasure of the women's lives from the national memory as the feminine aesthetic of scribal publication was overshadowed by the proliferating print culture of late eighteenth-century America.